Pre-clinical Evidence: Berberine as a Promising Cardioprotective Candidate for Myocardial Ischemia/Reperfusion Injury, a Systematic Review, and Meta-Analysis - Chen, Cong; Lin, Qian; Zhu, Xue-Ying; Xia, Junyan; Mao, Tianshi; Chi, Tiange; Wan, Jie; Lu, Jin-Jin; Li, Yan; Cui, Jie; Liu, Jing; Cui, Xiao-Yun; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: Myocardial ischemia/reperfusion (I/R) injury is one of the causes of most cardiomyocyte injuries and deaths. Berberine (BBR) has been suggested a potential to exert protective effects against myocardial I/R injury. This systematic review aims to determine the intrinsic mechanisms of BBR’s protective effects in myocardial I/R injury. Methods: Seven databases were searched for studies performed from inception to July 2020. Methodological quality was assessed by SYRCLE’s-RoB tool. Results: Ten studies including a total of 270 animals were included in this study. The methodology quality scores of the included studies ranged from 5 to 7 points. The meta-analysis we conducted demonstrated that BBR significantly reduced myocardial infarct size and the incidence of ventricular arrhythmia, compared to control groups (P < 0.00001). Cardiac function of animals in the BBR treatment group was also markedly increased (P < 0.00001). The index of myocardial apoptosis and the levels of biomarkers of myocardial infarction (LDH and CK) were also decreased in the BBR treatment groups compared to the control groups (P < 0.00001). Conclusions: The preclinical evidence, according to our study, showed that BBR is a promising therapeutic agent for myocardial I/R injury. However, this conclusion should be further investigated in clinical studies.